The Speculation of Conceptual Art—The "Dematerialization of Art " Phenomenon and the "End of Art " in the 1960s (Journal of Global Arts Studies, 2025)
Background: In the 1960s, European and American art witnessed diverse artistic styles and a strong trend toward “decentralization,” among which the “dematerialization of art” became particularly significant. Objective: This paper aims to conduct an in-depth analysis of the philosophical implications of conceptual art in the contemporary era. Methods: Taking the phenomenon of the “dematerialization of art” as the starting point and combining it with Danto’s theoretical perspective, this study explores the philosophical issues raised by conceptual art and reflects on Danto’s assertions and artistic pluralism. Results: The study finds that conceptual art shifts the core value of artworks from the sensory level to the intellectual level, raising philosophical questions concerning the nature of art. At the same time, it weakens the fixed structural framework traditionally assigned to art and promotes greater artistic diversity. Conclusion: Conceptual art plays an important role in advancing artistic innovation within the contemporary art context. The philosophical issues it generates will continue to provoke discussion and debate in both the present and the future.
Keywords: Dematerialization of Art; End ofArt; Lucy Lippard; Arthur Danto